دراسة تحليلية لأسباب الإصابات الرياضية لدى لاعبي فريق كرة القدم للناشئين بنادي وفاق صبراتة (Comprehensive Journal of Science, 2025)
This study analyzes the causes of sports injuries among youth football players at Wefaq Sabratha Club during the 2024–2025 season. The study aimed to identify the most common types of injuries and examine the effects of physical conditioning, training load, adherence to prevention programs, and psychological factors on injury rates. A descriptive-analytical method was employed, with the research population including all youth players aged 14–17, and a purposive sample of 18 players most exposed to injuries was selected. Data were collected from medical records, questionnaires, and interviews with technical and medical staff. Statistical analyses included frequencies, percentages, means, standard deviations, and Pearson correlation, with Cronbach’s alpha (α = 0.77–0.85) used to assess reliability.Results showed that muscular injuries were the most common (55.6%), followed by joint and structural injuries. A strong negative correlation was found between physical conditioning and injury rates, while a positive correlation existed between training load and injuries. Regular adherence to prevention programs reduced injury rates, and psychological stress had a moderate effect.The study concluded that improving physical conditioning, gradually adjusting training loads, enhancing prevention programs, and providing psychological support and medical monitoring are essential. Recommendations include training technical staff to implement preventive measures and raising awareness among players and parents to foster a safe and sustainable sporting environment..